Infinity in mathematics. Struggles with a necessary but troublesome concept - Murawski, Roman (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2014)
Infinity has appeared in mathematics since the very beginning. Moreover the mathematical concept of infinity was and is connected with philosophical and theological concepts. The aim of the paper is to show how mathematicians struggled with this concept and how they tried to bring it under control.